Atitudes e crenças sobre dor lombar em idosos da comunidade: dados do estudo BACE - Luiza Faria Teixeira (2015)
Introduction: Attitudes and beliefs are psychosocial factors known as yellow flags, which interfere in the context of low back pain (LBP). This condition is poorly studied in the elderly, specifically its acute form. The intensity of light and moderate DL tends to decrease with age while the intense and disabling pain is more likely to increase Attitudes and beliefs about LBP can influence this condition, increasing the risk of transition from acute to chronic back pain and development of long-term disability. The screening of psychosocial factors and knowledge of the factors associated to the onset of their outcomes is of fundamental importance for the prevention of the development of persistent and recurrent LBP and to assist effective interventions. The development of appropriate health policies with active strategies in psychosocial outcomes is important for maintaining the psychosocial well-being and prevention of disability in the elderly. Objective: To carry out cross-cultural adaptation of the Back Beliefs Questionnaire (BBQ) for Brazilian Portuguese in older adults with acute LBP, assess its internal consistency, compliance and intra and inter-rater reliability; explore the associated aspects (socio-demographic, clinical, self perceived health, psychosocial and emotional state, falls, disability, functional mobility and gait speed) to attitudes and beliefs at baseline and after 3, 6, 9 and 12 months. Method: Samples of the studies that make up this thesis were composed of a sub-sample of international epidemiological study BACE (Back Complaints in the Elders). The sample of the first study consisted of 26 seniors to cross cultural adaptation procedure and the intra and inter reliability were calculated using the intraclass correlation coefficient, the correlation by the standard error of measurement (SEM) and minimum detectable difference (MDD); and the internal consistency by Cronbach's alpha coefficient. The sample of the second cross-sectional study consisted of 532 elderly and to identify the variables associated with the outcome attitudes and beliefs about LBP a multiple regression analysis was performed. The sample of the third longitudinal study included 500 elderly and the association between the independent variables and the values of the BBQ was performed by multiple regression. Descriptive and univariate analyzes were performed, considering for all tests the significance level = 0.05 and used the Statistical Package for Social Sciences (SPSS 18.0 Chicago, IL, USA) for statistical analysis. Results: For the first study, the average age was 67.38 (± 5.76), 88.5% were women, the average BBQ for evaluator 1 was 23.81 (± 7.46) and 22.27 (± 8.44) for evaluator 2. The intra-rater reliability presented moderate rate of intra-class correlation - ICC = 0.73 (95% CI 0.49 to 0.87) and excellent interrater reliability, ICC = 0.91 (95% CI 0,81- 0.96). Regarding EPM and MDD, intra and inter measurements, the smallest error was detected by the ICC (2,1) for inter-rater reliability. The Cronbach's alpha showed an acceptable value of 0.70. For the second and third studies, 85.7% elderly were female and the average age was 69.04 (± 6.25). At the second cross-sectional study attitudes and beliefs were associated with disability, depressive symptoms and expected return to activities; and in the third longitudinal one, the following variables were associated with BBQ: disability, age, worse expectation of improvement and decreased mobility. Conclusion: BBQ showed adequate cross-cultural adaptation, reliable measures of reproducibility and reliability which proves to be a useful tool for clinical practice. Advanced age, disability, depressive symptoms, decreased mobility and expectation of improvement and return to activities were associated with attitudes and beliefs about LBP in the elderly at the moment of assessment and after a year of follow-up. The identification and tracking of these factors in elderly people who seek health care are key to preventing persistent LBP development and important for the design and planning of interventions by health professionals.